Epidemiological Trends of Malaria Cases in Rural Health and Training Centre Of Madhya Pradesh - Leena Balpande; Sanjay K Gupta; Sanjay S Agarwal (Medsci Publications, 2014)
Background: Malaria is a well-known disease and it continues to be a major public health problem at the start of new millennium. The problem is persistent not only amongst the city dwellers but also amongst the rural population. The problem in rural India is that the settlements are difficult to approach, road and transport facilities are minimal and health care facilities are scarce. The need of the study is to study the hospital based proportion of fever cases being diagnosed as malaria and determines the trend of malaria. Methods: A retrospective observational study was carried out at rural health and training centre at Ratua village regarding malaria cases, all suspected fever cases were reported to centre sent for peripheral blood examination in laboratory. Results: In the present study from (2006-2013) a total of 4454 (7%) fever suspected cases sent for malaria diagnosis in rural training health centre out of that 389(8.7%) came positive for malaria antigen. According to types of plasmodium species plasmodium vivax and Plasmodium falciparum accounted for 95.1% and 4.8% of malaria morbidity respectively. Malaria was reported in all age groups and both sexes, but the 11-20 year age group were affected more 93 (24%). Conclusion: P.vivax was the most common type of malaria. In the studied area malaria was common among males than females, commonly affected age group were between 11-20 years of age.